Մուստաֆա Քեմալ փաշան արևմտահայերի 1915—1916 թթ. ցեղասպանության մասին - Մ. Գ. Ներսիսյան (ՀՀ ԳԱԱ հրատ.)
Принятое в мае 1998 г. решение нижней палаты Национального собрания Франции— признать геноцид армян, как известно, подняло большой переполох и шум в Турции. Официальные круги страны начали резкие нападки против всех тех, кто говорит или пишет о том, что в 1915—1916 гг. в Османской империи был совершен геноцид западных армян. Турецкие власти считают врагами Турции всех, имеющих такое мнение. The decision accepted by the Lower House of the French National Assembly in May 1998 to recognize the genocide of the Armenians caused a big stir in Turkey. The official circles of the country started an attack against those who spoke or wrote about the fact of Genocide of the Western Armenians in Ottoman Empire in 1915—1916. Those who are of such an opinion are considered by the Turkish government as enemies of Turkey.
Keywords: History; Armenian Genocide (1915); D History